ANALYSIS OF INCREASED STUDENT MOTIVATION IN THE PROCESS OF LEARNING ENGLISH PRONUNCIATION - Sharon Ribka Berikang; Maya Pinkan Warouw; Muh. Hasan Basri (Universitas Sam Ratulangi, 2026)
This research is entitled “Analysis of Student Motivation Improvement in the English Pronunciation Learning Process.” This study aims to explore, analyze, and describe motivation in improving English pronunciation and the strategies used by English majors in improving English pronunciation. This study uses the concepts of Deci and Ryan (1980) and the Macrotheory of Deci and Ryan (2008). This type of research is descriptive research with a qualitative approach. In data collection, a semi-structured interview method was used. The results of the study show that: The factors that influence the increase in motivation of English major students in learning English pronunciation consist of two types of motivation, namely intrinsic and extrinsic motivation, such as: 1) intrinsic factors that influence the increase in student motivation, such as self-confidence, personal interests and goals, and self-motivation in learning English pronunciation. Then 2) extrinsic factors that influence the increase in student motivation, such as social and professional demands, peer influence, and support and encouragement from lecturers. Based on the results of the analysis of increased student motivation in the process of learning English pronunciation, several students emphasized that successful learning can occur due to motivating factors that arise from within themselves.